Evaluating the effect of iron sulphate on growth, yield, and physiological responses in wheat (Triticum aestivum L.) - Khair, Kashaf ul; Khalid, Zunaira; Ahmad, Muhammad; Aqib, Muhammad; Ahmed, Raza; Jabeen, Sundas; Azhar, Hira; Ahsan, Aneela (Journal of Pure and Applied Agriculture, 2025)
All creatures require iron (Fe) as a micronutrient. Plants often suffer from iron deficiency because iron has a low bioavailability in aerobic, calcareous, or high-pH soils. Wheat is staple food crop of our country, but its growth is often constrained by deficiencies of essential micronutrients, particularly copper, boron and iron, which require external supplementation for optimal plant development. To cope with this problem, a pot experiment was conducted in the Botanical Garden, Institute of Botany, University of the Punjab, Lahore, Pakistan. The experiment was laid out in a completely randomized design (CRD) under factorial layout with 03 replicates of 02 wheat varieties (Pakistan-2013 and Akbar-2019). Ferrous Sulphate (FeSO4.7H₂O) was applied through soil at concentrations of 10, 20, and 30 ppm, along with control were used. During this experiment, different morpho-physiological parameters, such plant height, leaf length, leaf width, leaf area, spike length, number of spikes per pot, number of spikelets per spike and number of leaves per pot, relative water content, total chlorophyll content and total carotenoids content, were noted. To assess the effect of FeSO4·7H₂O, antioxidant enzyme matrix activity, such as glutathione peroxidase (GPX) activity, ascorbate peroxidase (APX) activity, and catalase (CAT) activity were also determined. The result of wheat variety Akbar-2019 showed significantly high vegetative growth at 30 ppm while wheat variety, Pakistan-2013, showed the maximum growth at 20 ppm of FeSO4·7H₂O. The physiological parameters were maximum at 30 ppm of FeSO4·7H₂O for wheat variety Akbar-2019. Among the antioxidant enzymes, CAT and GPX exhibited maximal activity at 10 ppm FeSO₄·7H₂O in the Akbar-2019 variety, while APX reached its highest activity at 20 ppm in Pakistan-13, indicating varietal differences in Fe responsiveness. However, more investigation is required to carry out extended field studies at the molecular level to comprehend the underlying mechanisms.